Abdominal Wall Abscess due to Acute Perforated Sigmoid Diverticulitis: A Case Report with MDCT and US Findings. (9th December 2013) - Vasileios, Rafailidis; Anna, Gavriilidou; Christos, Liouliakis; Asimina, Tsimitri; Sofia, Paschaloudi; Vasiliki, Karadimou
Abstract : Perforation of the inflamed diverticula is a common diverticulitis complication. It usually leads to the formation of a local abscess. In some rare cases, the inflammatory process may spread towards extra-abdominal sites like the anterior or posterior abdominal wall or the thigh and form an abscess in these sites. We present the case of a 73-year-old man with a history of pain at the lower left quadrant of the abdomen for 20 days and a visible mass in this site. Ultrasonography and computed tomography revealed this mass to be an abscess of the abdominal wall which had been formed by the spread of ruptured sigmoid diverticulitis by continuity of tissue through the lower left abdominal wall. Local drainage of the abscess was performed and the patient was discharged after alleviation of symptoms and an uneventful course. We also discuss causes of abdominal wall abscesses along with the possible pathways by which an intra-abdominal abscess could spread outside the abdominal cavity.